If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2X + 3) = 6X + 9 Reorder the terms: 3(3 + 2X) = 6X + 9 (3 * 3 + 2X * 3) = 6X + 9 (9 + 6X) = 6X + 9 Reorder the terms: 9 + 6X = 9 + 6X Add '-9' to each side of the equation. 9 + -9 + 6X = 9 + -9 + 6X Combine like terms: 9 + -9 = 0 0 + 6X = 9 + -9 + 6X 6X = 9 + -9 + 6X Combine like terms: 9 + -9 = 0 6X = 0 + 6X 6X = 6X Add '-6X' to each side of the equation. 6X + -6X = 6X + -6X Combine like terms: 6X + -6X = 0 0 = 6X + -6X Combine like terms: 6X + -6X = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| (3x+8/5)-7=-x+9 | | 3(p+6q-14)= | | 3x+8/5-7=-x+9 | | 7x+9=7(x+8) | | 4/0.8=0.3/w | | 0.50X+0.35(70)=36.5 | | 0.9/0.5=z/4.5 | | 2x^2-0=14 | | 45/50=m/100 | | x/7=8/21 | | (x-5)(x^2+2x+5)= | | 6y+2-8y=3-2y-10 | | =-2(7+6n) | | -4(x-1)-(2-x)=-6 | | -5/9y-(y-5/6)=1/54(y-6) | | 16x+8y=-17 | | 8n+10-2n=3n-2+5n | | 8n+10-22=3n-2+5n | | -2x-10=4+5x | | -3-2x=18 | | 8(3w-7)=6(4w+5) | | -15+2m=-11 | | 1/6(10x-3)=7 | | -5+2m=11 | | (x/3)+(4x+6) | | 5x^2-38x+21= | | -15+10= | | 12*x+2*x+2=352 | | 12*x+2*x+2=0 | | 9-a/a+5=a/a+5 | | 14x+2=0 | | -6x^2-216x-600=0 |